Estado nutricional en niños de 2 a 5 años internados por otitis media aguda, en el servicio de pediatría del Hospital Belén de Trujillo - La Libertad, durante los meses octubre - diciembre, 2009 - Pashco Morillas, Maritza Janet (2017)
In the present study was determined nutritional status in children 2 to 5 years hospitalized for acute otitis media in the Department of Pediatrics of the Belen Hospital in Trujillo-La Libertad, during the months of October- December, 2009. Using the anthropometric method was evaluated in 72 children (27 boys and 45 girls) by the weight/height, height/age and Body Mass Index (BMI). According to the indicator weight/height the 62.5 % has a normal nutritional state, the 18.06% 16.67% obesity, acute malnutrition of first grade and the 2.78% acute malnutrition of second grade. In relation to height/age, 73.61% are in the normal parameter, and there is no delay in its size with regard to their age. However, the 20.84% had chronic malnutrition in first grade and the 5.56% chronic malnutrition in second grade. According to the BMI was found to be 59.72% have a normal BMI, the 25% low weight and the 15.28% overweight. The prevalence of malnutrition in children between 2 and 5 years is high and is a health problem, especially because of the susceptibility to respiratory infections